Real-time interactive volumetric animation of the heart's electrical cycle from automatically synchronized ECG - O'SULLIVAN, CAROL (My University, 2004)
We present a novel method for representing the electrical depolarisation and repolarisation of cardiac cells using real-time volumetric animation techniques. The visual representation coincides with automatically synchronized electrocardiogram (ECG) input. Whilst other projects in similar fields use super-computers or vastly complex cellular structures, one of the aims of this project is to simplify the process for real-time optimization. The current techniques are being used in a teaching tool and also are being implemented in a myocardial infarction diagnostic tool. Cellular automata are used to demonstrate the electrical progression with a multi-pass nearest-neighbour algorithm and automatic ECG recognition and detection algorithms are used to synchronize the animation with the inputted ECG. We use texture-based slices to represent the myocardial volume to improve speed.
PUBLISHED
Keywords: virtual reality; ECG simulation; cardiac modelling; Creative Technologies